1974
DOI: 10.1128/aac.5.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation Between Results of In Vitro and In Vivo Antibiotic Susceptibility Tests for Some Strains of Pseudomonas aeruginosa

Abstract: The relative efficacy in vivo of the polymyxin and aminoglycoside antibiotics in experimental Pseudomonas infection has apparently never been established. This study was designed to determine such efficacy in experimental infection of mice. Eleven strains of Pseudomonas aeruginosa were selected for the study, representing six of the seven recognized immunotypes. All strains were susceptible to colistin, gentamicin, and tobramycin in vitro, and all were virulent for mice. None was lethal because of preformed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…1 and 2). Our previous data (21) (23) have demonstrated that polymyxin has a higher affinity for Salmonella typhimurium lipopolysaccharide than does Mg2+, whereas others have demonstrated that moderately high levels of Mg2e are necessary to inhibit polymyxin activity (6). In the case of aminoglycosides, antagonism by Mg2e occurs at quite low Mg2e levels, and this competition tends to mask the protective effects of protein Hi when the protein is iriduced by growth in low Mg2".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2). Our previous data (21) (23) have demonstrated that polymyxin has a higher affinity for Salmonella typhimurium lipopolysaccharide than does Mg2+, whereas others have demonstrated that moderately high levels of Mg2e are necessary to inhibit polymyxin activity (6). In the case of aminoglycosides, antagonism by Mg2e occurs at quite low Mg2e levels, and this competition tends to mask the protective effects of protein Hi when the protein is iriduced by growth in low Mg2".…”
Section: Methodsmentioning
confidence: 99%
“…The discrepancy between in vitro and in vivo susceptibility is a major problem in aminoglycoside therapy (6,8). The well-documented antagonism of aminoglycosides by divalent cations (18,25) is one probable cause, and development of adaptive (nonmutational) resistance in vivo may also play a part.…”
mentioning
confidence: 99%
“…MATERIALS AND METHODS The methods were generally those previously described (3). Important changes will be noted.…”
mentioning
confidence: 99%
“…Colistimethate was relatively ineffective in the treatment of experimental keratitis by one strain of Pseudomonas. In an earlier study in mice, colistimethate was significantly less effective than tobramycin or gentamicin (2). In a more recent study (3), colistimethate was distinctly inferior in the mouse protection tests with four strains of P. aeruginosa when compared to polymyxin B sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate chemotherapy avoids a second dose of general anesthetic and is analogous to the usual method for the mouse protection test (2). In the future, we plan to evaluate the effects of delayed chemotherapy.…”
Section: Discussionmentioning
confidence: 99%